1997
DOI: 10.1002/jlac.199719970808
|View full text |Cite
|
Sign up to set email alerts
|

An Unorthodox Pathway to the 1,2‐Dithiin System

Abstract: Tetracyanoethylene combines with two molecules of thiobenzophenone in refluxing benzene to give the tetrasubstituted 1,2-dithiin 8 ( 2 1~2 9 % ) besides the corresponding thiophene derivative 9 (40-52%). The X-ray analysis of the ruby-red 8 reveals a half-chair conformation with a torsion angle of 58.9" at the disulfide bond. The thermal desulfurization 8 -+ 9 (benzonitrile, 100°C) proceeds with flI2 = 26.7 h, whereas the sulfur loss induced by triethyl phosphite is a billion times faster. The mechanisms of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 55 publications
0
6
1
Order By: Relevance
“…This result is quite different from that reported by Huisgen et al [3,6]. They have reported that the reaction of 1a with TCNE in refluxing chloroform afforded only 2a in 78% yield, and the reaction of thiobenzophenone (1b) with TCNE in refluxing benzene afforded 2b (Ar‫ס‬Ph) and 3b (Ar‫ס‬Ph) in 52% and 29% yields, respectively.…”
Section: Resultscontrasting
confidence: 76%
See 2 more Smart Citations
“…This result is quite different from that reported by Huisgen et al [3,6]. They have reported that the reaction of 1a with TCNE in refluxing chloroform afforded only 2a in 78% yield, and the reaction of thiobenzophenone (1b) with TCNE in refluxing benzene afforded 2b (Ar‫ס‬Ph) and 3b (Ar‫ס‬Ph) in 52% and 29% yields, respectively.…”
Section: Resultscontrasting
confidence: 76%
“…Another molecule of 4,4Ј-dimethoxythiobenzophenone (1a) reacted with 6 via a [4 ‫ם‬ 2] manner to afford the sixmembered cyclic disulfide (7), which finally extruded sulfur to give 5a. The formation mechanism of 2 had already been suggested by Huisgen et al [6]. The thioamide 6 was further attacked by another molecule of thiobenzophenone (1a) to yield maleonitrile and/or fumaronitrile derivatives (8).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…[110] Cycloadducts of sulfines with aliphatic thiones are more stable, this is shown by work carried out by Huisgen who isolated spiroadamantine-derived cycloadduct 94, and bis-spiroadamantane-derived cycloadduct 95 in high yields from cycloaddition reactions ( Figure 5). [111] Eur. J. Org.…”
Section: 3-dipolar Cycloadditionsmentioning
confidence: 99%
“…The synthesis of a series of differently substituted 1,2,4oxadithiolanes have been reported a few years ago in [2ϩ3] cycloadditions of aliphatic thioketones with dialkyl or diaryl sulfines; some of them were shown to convert into 1,2,4-trithiolanes on thermal decomposition. [4] While the both derived from the 1,2,4-oxadithiolane I, are proposed as elusive episulfidating agents.…”
Section: Introductionmentioning
confidence: 99%